(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Alice Walker’s Pulitzer Prize-winning novel, The Color Purple, is a celebrated masterpiece in Afro-American literature. Through her writing, Walker gives voice to marginalized communities, capturing their struggles, culture, and resilience. With vivid storytelling, she weaves together the experiences, traditions, and emotions of Afro-Americans, creating a powerful narrative that resonate globally. Walker has always championed the right to live freely and fearlessly, as she says, "I am preoccupied with the spiritual survival, the survival whole of my people. But beyond that I am committed to exploring the oppressions, the insanities, the loyalties and the triumphs of black women." (ISMG 250,-51) This paper explores how Alice Walker portrays Celie’s transformative journey in "The Color Purple", from being a powerless victim of societal oppression to achieving empowerment. Through Celie’s story, Walker illustrates the path from self-denial to self-discovery, highlighting the resilience and strength of a marginalized black woman in a patriarchal society.